2016
DOI: 10.1182/blood.v128.22.2639.2639
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Activation Is Not Crucial for Platelet-Rich Plasma (PRP), When Used As Autologous Therapeutic Product, and Could be Lyophilized without Any Growth Factor Loss

Abstract: Platelet-rich Plasma (PRP) has been widely used in different fields of medicine as autologous therapeutic product. The main component that appears to be associated with the therapeutic effect is the presence of growth factors (GF). However, many protocols available induce high methodology variability. In addition, is still unclear what is the best platelet activator and the necessity for the clinical practice. The traditional PRP used (Fresh PRP) can vary to each preparation and it has also been difficult to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Some studies suggest that platelets in blood samples become activated by several conditions of preparation, such as manual manipulation, temperature, and the pressure to which the platelet is subjected inside the needle, among others. This confirms that platelet activation with thrombin or calcium chloride before PRP application is not crucial [15]. At the end of this point assessment, there is also existing evidence that platelets after injection in human deep dermis and immediate subdermis become activated by contact with fibroblasts [16] which induces soft tissue augmentation, new collagen deposition, as well as new blood vessels and adipose tissue formation [17].…”
Section: Discussionsupporting
confidence: 70%
“…Some studies suggest that platelets in blood samples become activated by several conditions of preparation, such as manual manipulation, temperature, and the pressure to which the platelet is subjected inside the needle, among others. This confirms that platelet activation with thrombin or calcium chloride before PRP application is not crucial [15]. At the end of this point assessment, there is also existing evidence that platelets after injection in human deep dermis and immediate subdermis become activated by contact with fibroblasts [16] which induces soft tissue augmentation, new collagen deposition, as well as new blood vessels and adipose tissue formation [17].…”
Section: Discussionsupporting
confidence: 70%
“…Nevertheless, platelet activation through the addition of an exogenous agonist is not as crucial as mechanical trauma (generated through centrifugation force or freezing thawing process that can break the platelets membrane) [Spreafico et al, 2009;Sumner et al, 2017] and lyophilizing the PRP are able to trigger spontaneous platelet activation [Stukelj et al, 2017]. Interestingly, this spontaneous activation preserved the concentration of secreted bioactive molecules [Silva et al, 2016]. In vivo studies have also reported on the positive effect of nonactivated PRP in alleviating knee OA [Kanwat et al, 2019;Bennell et al, 2021].…”
Section: Discussionmentioning
confidence: 99%